Sugar and Auxin Signaling Pathways Respond to High-Temperature Stress during Anther Development as Revealed by Transcript Profiling Analysis in Cotton . Issue 3 (30th January 2014) - Min, Ling; Li, Yaoyao; Hu, Qin; Zhu, Longfu; Gao, Wenhui; Wu, Yuanlong; Ding, Yuanhao; Liu, Shiming; Yang, Xiyan; Zhang, Xianlong
Abstract : Anther indehiscence at high temperatures is coordinately regulated by sugar and auxin . Abstract: Male reproduction in flowering plants is highly sensitive to high temperature (HT ). To investigate molecular mechanisms of the response of cotton ( Gossypium hirsutum ) anthers to HT, a relatively complete comparative transcriptome analysis was performed during anther development of cotton lines 84021 and H05 under normal temperature and HT conditions. In total, 4, 599 differentially expressed genes were screened; the differentially expressed genes were mainly related to epigenetic modifications, carbohydrate metabolism, and plant hormone signaling. Detailed studies showed that the deficiency in S-ADENOSYL-l -HOMOCYSTEINE HYDROLASE1 and the inhibition of methyltransferases contributed to genome-wide hypomethylation in H05, and the increased expression of histone constitution genes contributed to DNA stability in 84021. Furthermore, HT induced the expression of CASEIN KINASEI ( GhCKI ) in H05, coupled with the suppression of starch synthase activity, decreases in glucose level during anther development, and increases in indole-3-acetic acid (IAA ) level in late-stage anthers. The same changes also were observed in Arabidopsis ( Arabidopsis thaliana ) GhCKI overexpression lines. These results suggest that GhCKI, sugar, and auxin may be key regulators of the anther response to HT stress. Moreover, PHYTOCHROME-INTERACTING FACTOR genes ( PIFs ), which are involved in linking sugar and auxin and are regulated by sugar, might positively regulate IAA biosynthesis in the cotton anther response to HT . Additionally, exogenous IAA application revealed that high background IAA may be a disadvantage for late-stage cotton anthers during HT stress. Overall, the linking of HT, sugar, PIFs, and IAA, together with our previously reported data on GhCKI, may provide dynamic coordination of plant anther responses to HT stress.